2009
DOI: 10.2481/dsj.br-07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Dose Chronic Radiation and Heavy Metals on Plants and Their Fungal and Virus Infections

Abstract: The effects of low dose chronic radiation on plant disease resistance and fungal and virus infections have been studied. The results obtained in the 10-km Chernobyl zone demonstrated a decrease in plant disease resistance and appearance of a "new" population of stem rust agents of cereal with a high frequency of more virulent clones. Radionuclide contamination and heavy metals lead to wider virus spread and a higher diversity of virus species. The Chernobyl zone is a territory of enhanced risk and potential th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Like the cereal species, the transfer factor was in direct proportion with the received dose. Regarding the chronic dose impact study to the plant, activity of proteinase enzyme inhibitors in grains of wheat and rye was decreased to 30-55% as compared to a control study [22]. Sparrow et al…”
Section: Discussionmentioning
confidence: 96%
“…Like the cereal species, the transfer factor was in direct proportion with the received dose. Regarding the chronic dose impact study to the plant, activity of proteinase enzyme inhibitors in grains of wheat and rye was decreased to 30-55% as compared to a control study [22]. Sparrow et al…”
Section: Discussionmentioning
confidence: 96%
“…If we compare the obtained dose range to the wild grass (worldwide), it could be said that there can be a potential negative impact on the growth of the plants. Dmitriev et al (23) had studied the mutation due to radiation and had predicted that it is a useful tool to know the chronic type radiation impact at certain dose ranges. The studies in an area contaminated as a result of the Chernobyl accident (1986)(1987)(1988), seeds of timothy-grass (Phleum pratense L.) were additionally exposed to probing acute gamma radiation in different doses and it wound that 20 Gy (5 mGyd 21 ) and 80 Gy (240 mGyd 21 ) stimulation of growth processes was observed (23,24) .…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the activity of proteinase inhibitors (trypsin, chymotrypsin, subtilisin) in plants grown on radionuclide-contaminated plots was significantly decreased. In wheat and rye grains the activity was decreased by as much as 15-60% compared to the control [119]. It is not clear, however, whether other plant defence responses (phytoalexin synthesis and/or accumulation of PR-proteins) could also be affected by low-dose chronic radiation.…”
Section: Chernobyl Contamination and Resistance Of Plants To Fungi Anmentioning
confidence: 94%
“…Plant viruses are less numerous than fungal pathogens but they also could be harmful if the transformed environment were to facilitate virus infections. It was shown that ionising radiation and heavy metal contamination of soil may lead to significant changes in symptoms induced by virus infection, elevation of virus content in plants, and possibly mutations in plant virus genomes [119,124,126]. Chemical stress factors including heavy metals and radionuclides are known to induce various biologically significant phenomena in the course of viral disease.…”
Section: Chernobyl Contamination and Resistance Of Plants To Fungi Anmentioning
confidence: 99%
See 1 more Smart Citation